Elementos para a educação de pessoas velhas - Capuzzo, Denise de Barros (2012)
Considering the increasing life expectancy and engagement of older people by seeking their rights and existing public policies, I noticed the significant demand in education for these people, aiming at universal access to knowledge, thus opening programs Open Universities of the Third Age. As a consequence, the question arises: Who are the professionals responsible for the education of the elderly? There is a teacher training specific to old people? From these questions, we sought a methodology that would favor this research. I chose a qualitative study, consisting of literature review, document analysis, observations and field diaries and interviews. In order to highlight elements that could contribute to think, question and discuss the education of people of various old documents analyzed UnATIs run, I tried to investigate, identify students / educators and the / the two programs UnATIs run, trying to discuss the contents, prioritized themes and goals of these programs, in addition to student motivation / as well as the dynamics of teaching practice with older people. After data analysis and effort to establish connections, mediations and contradictions with the theory concludes that educators old people must have the technical skills, scientific and policies to carry out its activities, so training in gerontology becomes recommendable. A striking aspect well in educational practice with older people is affection, both in terms between educator / student ae / ae among students / as. The research also showed me that the exchange of life experiences that also have emotional aspects involved in this process is critical teaching and learning. Other significant elements are: the language of the educator / a, the character of the proposed activities that should result in immediate and practical benefit and the prospect of enhancing and / or mediate the construction of citizenship and autonomy. The data collected allow me to say that old people who seek programs aimed at seniors, are not only in search of adaptation to social reality, but to be active in this process, intervention and transformation of their realities.